Water Masses, circulation and transport in the eastern boundary current of the North Atlantic subtropical gyre - Hernández-Guerra, A.; López Laatzen, F.; Machin, F.; Armas, Demetrio de; Pelegrí Llopart, José Luis (2018)
CTD sections carried out in September 1998 are used to describe the water masses, geostrophic circulation and mass transport in the eastermmost branch of the Canary Current.The surface water mass (<600m) consists of North Atlantic Central Water (NACW) flowing south with a net mass transport of 2.3 x 10 (9)kg s(-1). A tongue of relatively fresh water, consisting of Antarctic Intermediate Eater (AAIW). was found approximately in the 600-1100 m depth layer. This tongue was 200 km wide, stretching from the African coast almost to Gran Canaria Island, and transported a net mass of 1.1 x 10 (9) Kg s(-1) northward. This system of currents is what constitutes the real eastem boundary current of the North Atlantic Subtropical Gyre.